Protective effect of Nigella sativa L. (black cumin) seed oil on sodium valproate-induced neural tube defects and behaviour in mice model - Shiitu, Bello Sirajo (2017)
Neural tube defects (NTDs) are the major congenital malformations of the central nervous system in humans. The universal occurrence of neural tube defects (NTDs) ranges from 0.5 to 12 per 1000 live births depending on the countries, with higher incidence in the developing countries; this accounts for 400,000 live births globally per annum. Women of childbearing age with epilepsy are often concerned about hazards of drug exposure during pregnancy and lactation. Valproic acid (VPA) an antiepileptic drug causes teratogenicity and embryo toxicity, when taken during pregnancy. Plant extracts has been in use to prevent and treat different diseases, Nigella sativa L. (NS) is a family member of the Ranunculaceae that has been in use as food additives to prevent different types of diseases. Effect of NS extract on central nervous system has been studied by many researchers and most of the studies have shown positive outcome and good benefit on the central nervous system. This study was done to evaluate the effects of NS oil extract on the prevention of sodium valproate-induced neural tube defects in mice, and the developmental impairment induced by sodium valproate exposure during intrauterine stage. Seventy five (60 female and 15 male), non-gravid ICR mice were used for the study. The mice at 7 weeks of age were allowed two weeks of adjustment in the animal house. In the first study, gravid mice were divided into five groups of six pregnant mice each. Group 1 was treated with VPA only at a dose of 600mg/kg daily, groups 2, 3 and 4 receivedVPA at a dose of 600mg/kg/day + 0.2ml of NS oil extract, VPA at a dose of 600mg/kg/day + 0.1ml of NS oil extract and 600mg/kg/day + FA 400μg, respectively. Group 5 mice were administered with 0.9% saline, and served as control. The dams were sacrificed on gestational day 15 and the embryos were harvested for physical examination and laboratory evaluation. The treatment regimens for Groups 1, 2, 4 and 5 were repeated in the second study, with the exclusion of Group 3. The offspring from these groups were assessed at 3-7 weeks old for physical developmental milestones and evaluated for various behavioural tests. Muscle weakness, memory impairment and anxiety were ameliorated in the offspring that had been treated with NS oil extract plus VPA, compared to those treated with VPA only, and VPA + FA. Animals in the Control group did not have any evidence of muscular and memory deficits. Light microscopy histological evaluation illustrated that there were significant distortion in the architecture of the cell in the spinal cord in VPA only, and VPA + FA groups. There was no significant distortion observed in VPA + NS 0.2 ml group. Nuclear swelling and necrosis associated with VPA exposure seen on TEM images was significantly reduced by NS oil extract supplemented at 0.2 ml. The inhibition of histone deacetylase (HDAC) by VPA was significantly reversed in the VPA + NS 0.2 ml treatment group.In conclusion, this study demonstrated that administration of NS oil extract improved memory and learning abilities in offspring that had shown disabilities associated with prenatal exposure to sodium valproate. The NS oil extract is also beneficial in improving the muscular strength, and reversal of anxiety and behavioural deficits associated with in utero VPA exposure. It is postulated that the administration of NS oil extract prevented NTDs associated with prenatal VPA exposure, by reducing the inhibition of HDAC activity associated with VPA exposure.